2012
DOI: 10.1159/000335602
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Lapsed German Whole Blood Donors and Barriers to Return Four Years after the Initial Donation

Abstract: Background: The aim of the study was to identify characteristics of lapsed donors 4 years the initial donation as well as self-reported barriers to return for further blood donations. Methods: A random number of 8,000 blood donors, donating for the German Red Cross Blood Service Baden-Württemberg – Hessen, were asked to fill in a self-administered questionnaire. The response rate was 38.5%. Donors were categorized as ‘lapsed’ if they had not donated within the last 24 months. The odds of being a lapsed donor w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 19 publications
2
22
1
2
Order By: Relevance
“…These findings are in contrast to previous studies that underline the relevance of 1st year donation frequency for long-term donor retention [13,16]. Schreiber et al [16] demonstrated that further donations in the first months following the initial blood donation significantly increase the likelihood of becoming a regular blood donor.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…These findings are in contrast to previous studies that underline the relevance of 1st year donation frequency for long-term donor retention [13,16]. Schreiber et al [16] demonstrated that further donations in the first months following the initial blood donation significantly increase the likelihood of becoming a regular blood donor.…”
Section: Discussioncontrasting
confidence: 87%
“…The analytic sample consisted of 3,649 donors (sample 1 = 2,935 and sample 2 = 714). In both samples, donors who did not participate in the survey tended to be younger, male, and donated less frequently after the initial donation than participating donors [13]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The retention and motivation of active donors has thus been described as one of the major challenges for Blood Donor Services to secure the estimated demand for transfusions [4,5]. A significant proportion of active donors, however, stop donating blood at one point in their donor career for no obvious reason [6,7].…”
Section: Introductionmentioning
confidence: 99%